Coverless information hiding method based on the keyword. (8th May 2019) - Ji, Hongyong; Fu, Zhangjie
Information hiding is an important technique to make secure the transmission of information. However, the existing information hiding method based on text is difficult to resist various steganography detection. Coverless text information hiding, a new information-hiding technique, is presented in this paper to ensure data security. Firstly the presented method selects the appropriate natural text as information carrier from the big data, and then generates the plaintext automatically by the natural text and the prior agreement. The method we propose can resist many types of existing steganalysis. The experimental results show that this method is effective.